Alumina ceramic material, method for preparing the same and use thereof
Patent Information
- Application Number
- CN202410800590.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-20
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-06-20
AI Technical Summary
虽然可以便利地得到结构复杂的陶瓷、显著降低生产成本,且制得的陶瓷材料绝缘能力强、耐高温、耐老化能力强,具有较强的灭弧能力,可大程度提高继电器等工件的使用寿命;但是陶瓷浆料中白蜡含量较大,排蜡过程中气孔无法完全排出,收缩率较大,导致陶瓷材料密度相对较低,气密性亦无法得到很大的提升,在高电压绝缘系统中易发生沿面闪络现象的问题
[0048]1、本发明提供一种氧化铝陶瓷材料,所述氧化铝陶瓷材料的原料包括:氧化铝90wt%-94.9wt%,氧化铬2wt%-4wt%,掺杂剂0.1wt%-2wt%,助烧剂1wt%-4wt%,二氧化硅1wt%-4wt%,碳酸锰1wt%-2wt%,所述掺杂剂为氧化锶、氧化钛、氧化钡中的至少一种。本发明制备的氧化铝陶瓷材料的密度≥3.83g/cm3,致密度达96%,洛氏硬度≥90HRA,耐磨性优异,表面颜色均匀。
Smart Images

Figure CN118851730B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ceramic materials technology, specifically to an alumina ceramic material, its preparation method, and its application. Background Technology
[0002] Alumina ceramics are one of the most widely used advanced ceramic materials. Due to their excellent flexural strength and extremely high tensile strength, they are widely used in national economic sectors such as aerospace, aviation, power, electronics, machinery, chemical industry, petroleum, mining, and automobiles, as well as in national defense and military fields.
[0003] The application of ceramic materials in relays is becoming increasingly common. Ceramic vacuum relays consist of a housing and an energizing mechanism housed within it. Conductive posts connected to the energizing mechanism are fixedly mounted on the upper surface of the housing. The connection between the ceramic housing and the conductive posts requires metallization of the ceramic material, followed by sealing welding. During this process, Kovar, a high-melting-point material, easily generates a large amount of heat, causing significant thermal stress on the ceramic substrate and making it prone to cracking. Therefore, high strength of the ceramic substrate is required. Simultaneously, since high voltage is applied between the two conductive posts during operation, generating an electric arc, the vacuum ceramic housing serves to extinguish this arc. If air is present inside the ceramic housing, it can easily ionize, generating electric sparks and rendering the device unusable. Therefore, high airtightness is required for the ceramic housing material. Existing purplish-red alumina ceramic relay housings have poor density, and their airtightness is easily compromised under certain ultra-high voltage conditions. White ceramic relay housings have good airtightness but poor corrosion resistance, are prone to half-spots during manufacturing, and are susceptible to aging and discoloration, resulting in a limited lifespan.
[0004] Existing technology discloses a ceramic slurry, its preparation method, and a ceramic material. The ceramic slurry comprises the following components in parts by weight: 93.5 parts alumina, 1.1-1.8 parts silicon dioxide, 3.0-3.2 parts calcium carbonate, 1.2-1.7 parts kaolin, 1-2 parts colorant, and 11-12.5 parts beeswax. The preparation method involves ball milling each component in a ball mill to obtain a mixed powder; then adding beeswax to the mixed powder and mixing thoroughly to obtain the ceramic slurry. The ceramic material is prepared from the above-mentioned ceramic slurry. Although it can conveniently produce ceramics with complex structures, significantly reduce production costs, and the resulting ceramic material has strong insulation, high temperature resistance, strong aging resistance, and strong arc-extinguishing ability, which can greatly improve the service life of relays and other components, the ceramic slurry has a high beeswax content. During the wax removal process, the pores cannot be completely discharged, resulting in a large shrinkage rate. This leads to a relatively low density of the ceramic material, and the airtightness cannot be greatly improved. In high-voltage insulation systems, it is prone to surface flashover.
[0005] Therefore, it is necessary to provide a ceramic material with high density, high strength, high flashover voltage, and suitable for metallization, which is an urgent technical problem to be solved in this field. Summary of the Invention
[0006] In view of this, the present invention provides an alumina ceramic material with high density, high strength, and high flashover voltage, suitable for metallization.
[0007] The present invention also provides a method for preparing the above-mentioned alumina ceramic material.
[0008] In a first aspect, the present invention provides an alumina ceramic material, wherein the raw materials of the alumina ceramic material, by weight percentage, include: 90wt%-94.5wt% alumina, 2wt%-4wt% chromium oxide, 0.4wt%-2wt% dopant, 1wt%-4wt% sintering aid, 1wt%-4wt% silicon dioxide, and 1wt%-2wt% manganese carbonate.
[0009] The dopant includes at least one of strontium oxide, titanium oxide, and barium oxide.
[0010] In one optional embodiment, the dopant is strontium oxide, and the content of strontium oxide is 0.4wt%-1wt%.
[0011] In one optional embodiment, the dopant is titanium oxide, and the content of titanium oxide is 0.4wt%-1wt%.
[0012] In one alternative embodiment, the dopant is barium oxide, and the content of titanium oxide is 0.4 wt%-1 wt%.
[0013] In one optional embodiment, the dopant is strontium oxide and titanium oxide, wherein the content of strontium oxide is 0.4 wt%-1 wt% and the content of titanium oxide is 0.4 wt%-1 wt%.
[0014] In one alternative embodiment, the sintering aid includes at least one of calcium carbonate, calcium oxide, and magnesium oxide.
[0015] Secondly, the present invention provides a method for preparing the above-mentioned alumina ceramic material, comprising the following steps:
[0016] (1) Weigh the raw materials of the alumina ceramic material, mix them, and obtain a solid mixture;
[0017] (2) The solid mixture is calcined, ball-milled, and granulated to obtain powder;
[0018] (3) The powder is pressed and sintered to obtain the alumina ceramic material.
[0019] In one alternative implementation, the sintering step includes a heating process and a cooling process.
[0020] In one optional embodiment, the heating process includes raising the temperature to a first temperature zone of 200℃-260℃, a second temperature zone of 500℃-600℃, a third temperature zone of 800℃-1000℃, a fourth temperature zone of 1200℃-1400℃, and a fifth temperature zone of 1450℃-1650℃.
[0021] In one optional embodiment, the cooling process includes: cooling the temperature to 700°C-1000°C and then cooling it to room temperature along with the furnace.
[0022] In one optional implementation, the heating rate of the first temperature zone, the second temperature zone, the third temperature zone, the fourth temperature zone, and the fifth temperature zone is 1℃ / min-5℃ / min.
[0023] In one optional embodiment, the cooling rate is 1°C / min to 8°C / min.
[0024] In one optional implementation, the heat preservation time of the first temperature zone is 2h-6h.
[0025] In one optional implementation, the heat preservation time of the second temperature zone is 1h-3h.
[0026] In one optional implementation, the heat preservation time for the third and fourth temperature zones is 0.5h-1h.
[0027] In one optional implementation, the heat preservation time of the fifth temperature zone is 2h-6h.
[0028] In one optional embodiment, in step (2), after the solid mixture is calcined, defoamer, dispersant and deionized water are added and mixed, then ball-milled, and then a binder is added for granulation to obtain powder.
[0029] In one optional embodiment, the defoamer includes at least one of tributyl ester solution, polydimethylsiloxane solution, and polyoxypropylene solution.
[0030] In one alternative embodiment, the dispersant comprises at least one of a polyammonium methacrylate solution, a polyacrylic acid solution, and a sodium polyacrylate solution.
[0031] In one alternative embodiment, the adhesive comprises at least one of polyvinyl alcohol, polyethylene glycol, and sodium carboxymethyl cellulose.
[0032] And / or, the mass ratio of the solid mixture, the defoamer, the deionized water and the binder is 100:0.05-0.1:150-200:3-5.
[0033] In one alternative embodiment, the dispersant is added until the viscosity decreases to below 4000 mPa·s, at which point the addition of the dispersant is stopped.
[0034] In one optional embodiment, the defoamer has a mass concentration of 30%-40%.
[0035] In one optional embodiment, the mass concentration of the dispersant is 30%-35%.
[0036] In one optional embodiment, the calcination temperature is 600℃-800℃, and the calcination time is 3h-6h.
[0037] In one optional embodiment, the ball milling time is 30-36 hours.
[0038] In one optional embodiment, the particle size of the powder is 40μm-130μm.
[0039] In one optional embodiment, the pressing step is at least one of isostatic pressing and dry pressing.
[0040] In one optional embodiment, prior to the molding process, a compaction step is further included, wherein the compaction frequency is 15Hz-30Hz.
[0041] In one alternative implementation, the cooling process is followed by finishing and polishing steps.
[0042] In one optional embodiment, the isostatic pressing pressure is 150MPa-300MPa, and the holding time is 3min-10min.
[0043] In one optional embodiment, the pressure of the dry pressing is 50MPa-90MPa, and the holding time is 3min-5min.
[0044] Thirdly, the present invention provides a ceramic material for a relay housing, including the aforementioned alumina ceramic material.
[0045] Fourth invention: The present invention provides a relay comprising the aforementioned relay housing ceramic material.
[0046] During high-temperature sintering, chromium oxide (Cr2O3) is oxidized to form volatile CrO3. Inevitably, some chromium will volatilize in the air, making it impossible for chromium oxide to completely dissolve in aluminum oxide. Sintering in a hydrogen atmosphere can yield a more ideal product, but the cost is high.
[0047] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0048] 1. This invention provides an alumina ceramic material, the raw materials of which include: 90wt%-94.9wt% alumina, 2wt%-4wt% chromium oxide, 0.1wt%-2wt% dopant, 1wt%-4wt% sintering aid, 1wt%-4wt% silicon dioxide, and 1wt%-2wt% manganese carbonate. The dopant is at least one selected from strontium oxide, titanium oxide, and barium oxide. The alumina ceramic material prepared by this invention has a density ≥3.83 g / cm³. 3 It has a density of 96%, a Rockwell hardness of ≥90HRA, excellent wear resistance, and a uniform surface color.
[0049] This invention incorporates titanium dioxide and / or strontium oxide, both nanoscale powders, which primarily occupy grain boundary positions during the reaction. These grain boundaries act as pinning agents, inhibiting chromium oxide diffusion, promoting the solid solution of chromium oxide and aluminum oxide, suppressing anisotropic grain growth, and improving the density and Rockwell hardness of the ceramic material. Furthermore, strontium oxide or barium oxide can dissolve into the sintering aid's unit cell to form a solid solution, leading to lattice distortion of the aid, increasing the sintering activity of the material, and promoting solid-phase reactions. The solid solution then reacts with silicon dioxide to form a complex phase (Ca). 1.97 Sr 1.03 Al2O6 can promote the sintering of materials. On the other hand, the complex silicate phase has a low melting point and exists in the pores between the main crystalline phase particles. While filling the pores, it is conducive to the diffusion of materials and synergistically improves the density and Rockwell hardness of the materials. At the same time, the strength of the material formed by strontium oxide or barium oxide is higher than that of the glass phase, which improves the grain boundary strength and the overall fracture strength of the material, suppresses grain anisotropy, and ensures uniform grain size and balanced material performance.
[0050] This invention incorporates manganese carbonate, Al2O3, and MnCO3 to form MnAl2O4. The doped Cr2O3, in conjunction with MnAl2O4, can reduce the resistivity of the ceramic material. Simultaneously, Cr... 3+ The secondary electron emission coefficient of ceramic materials is reduced. While maintaining the insulation performance of alumina ceramics, the incorporation of Cr2O3-MnCO3 can effectively improve the surface flashover voltage of ceramics and improve their breakdown performance.
[0051] The addition of chromium oxide in this invention can enhance the wear resistance of alumina ceramics; the addition of titanium dioxide can also make the ceramic material reddish-brown, making the color more mellow and textured, which is beneficial to subsequent metallization processing, and maintain its glass phase content at 4.8%-5.4%, which is suitable for metallization processes.
[0052] 2. This invention provides a method for preparing alumina ceramic materials. The heating process of this invention includes five temperature zones: a first temperature zone of 200℃-260℃, a second temperature zone of 500℃-600℃, a third temperature zone of 800℃-1000℃, a fourth temperature zone of 1200℃-1400℃, and a fifth temperature zone of 1450℃-1650℃. The heating rate of the first, second, third, fourth, and fifth temperature zones is 1℃ / min-5℃ / min. The first and second temperature zones are for the debinding process, and setting the heating rate to 1℃ / min-5℃ / min is beneficial for the removal of binders from the powder. The binder is completely removed; the third and fourth temperature zones are for the removal of pores, and the heating rate is set at 1℃ / min-5℃ / min to facilitate the removal of pores and reduce through-holes; the fifth temperature zone is the sintering process, where solid-state reactions occur inside the material, grains grow, and gradually form ceramics; the melting point of the fifth temperature zone is close to that of complex silicate phases, so it will not form a liquid phase like the sintering aid, and its diffusion is relatively slow. During the crystal growth process, it can suppress the anisotropic growth of grains, so that the resulting grains are mostly equiaxed, which is also conducive to suppressing the continuous expansion of larger grains, while suppressing crack propagation, so that the grain distribution after sintering is more uniform.
[0053] The main component of the ceramic material of this invention is alumina. The process is simple, the sintering temperature is below 1700℃, the requirements for the sintering furnace are low, and the preparation cost is low.
[0054] 3. The present invention provides a method for preparing alumina ceramic material. The preferred molding step is isostatic pressing, which ensures uniform pressure and uniform material shrinkage. For irregularly shaped parts, the deformation is small, which can ensure uniform material properties and facilitate subsequent precision machining. Attached Figure Description
[0055] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0056] Figure 1 This is a scanning electron microscope image of Embodiment 1 of the present invention. Detailed Implementation
[0057] The following embodiments are provided to better understand the present invention and are not limited to the preferred embodiments described. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.
[0058] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.
[0059] The present invention will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed by the present invention.
[0060] The polydimethylsiloxane used in this invention was purchased from Guangzhou Tianfeng Defoamer Co., Ltd., model DP-281; polyoxypropylene was purchased from Jiangsu Haian Petrochemical, model DU-619; polyacrylic acid was purchased from Henan Jijia Chemical, model L-047; ammonium polymethacrylate was purchased from German Sima Chemical, model CE-64; sodium polyacrylate was purchased from Wuxi Fengmin Environmental Protection Technology Development Co., Ltd., model FMX-26; polyvinyl alcohol was purchased from Shanghai Jinchun Industrial Co., Ltd., model 088-50; polyethylene glycol was purchased from Jinan Xinshengguan Trading Co., Ltd., molecular weight 6000, model PEG6000; and sodium carboxymethyl cellulose was purchased from Hebei Haizuan Petrochemical, model CMC-HV.
[0061] Example 1
[0062] This embodiment provides a method for preparing alumina ceramic materials, including the following steps:
[0063] (1) Weigh aluminum oxide, chromium oxide, calcium carbonate, silicon dioxide, titanium oxide and manganese carbonate in a mass ratio of 92:2.5:2.5:1:1:1, with a total mass of 75g. After mixing, a solid mixture is obtained.
[0064] (2) After calcining the solid mixture at 600℃ for 3h, add 120mL of deionized water, 0.07g of tributyl ester with a mass concentration of 40% and polymethyl methacrylate (CE-64) with a mass concentration of 30%. When adding CE-64, the viscosity is measured dropwise by a rotational viscometer until the viscosity is reduced to 4000mPa·s. The mixture is then ball-milled for 36h using a planetary ball mill. The slurry is then removed, and 3g of polyvinyl alcohol is added. The mixture is then granulated using a spray granulator to obtain powder with a particle size mainly distributed in the range of 60μm-120μm.
[0065] (3) The above powder is loaded into an isostatic square silicone mold, placed on a vibration platform and vibrated at a frequency of 30Hz, and then transferred to an isostatic pressing equipment for isostatic pressing molding; wherein, the pressure of isostatic pressing is 200MPa and the holding time is 5min.
[0066] (4) After molding, the green body is machined into a grooved shape and placed in an electric furnace for high-temperature sintering. The sintering process includes sequential heating and cooling treatments, specifically: heating from room temperature to 250℃ at a heating rate of 5℃ / min and holding for 3 hours; heating to 500℃ at a heating rate of 5℃ / min and holding for 1 hour; heating to 900℃ at a heating rate of 5℃ / min and holding for 0.5 hours; heating to 1350℃ at a heating rate of 3℃ / min and holding for 0.5 hours; heating to 1580℃ at a heating rate of 1℃ / min and holding for 4 hours; then cooling to 800℃ at a heating rate of 5℃ / min and cooling to room temperature in the furnace; finally, after finishing and polishing, the ceramic material is obtained. Scanning electron microscopy shows... Figure 1 As shown in the figure, the grains are relatively evenly distributed.
[0067] Example 2
[0068] This embodiment provides a method for preparing alumina ceramic materials, including the following steps:
[0069] (1) Weigh aluminum oxide, chromium oxide, calcium carbonate, silicon dioxide, titanium oxide, strontium oxide and manganese carbonate in a mass ratio of 91:3:2.5:1:1:0.5:1, with a total mass of 90g. After mixing, a solid mixture is obtained.
[0070] (2) The solid mixture was calcined at 600℃ for 3h, and 150mL of deionized water, 0.05g of 40% tributyl ester and 30% polymethyl methacrylate (CE-64) were added. When adding CE-64, the viscosity was measured dropwise with a rotational viscometer until the viscosity decreased to 3600mPa·s. The mixture was then ball-milled for 32h using a planetary ball mill. The slurry was removed, and 4g of polyethylene glycol was added. The mixture was then granulated using a spray granulator to obtain powder with a particle size of 70μm-130μm.
[0071] (3) The above powder is loaded into a dry-pressed cylindrical mold, placed on a vibration platform and vibrated at a frequency of 30Hz, and then transferred to a dry-pressing equipment for dry-pressing. The pressure of the dry press is 55MPa, the holding time is 3min, and the dry-pressed round block is taken out.
[0072] (4) After forming, the green body with round holes is machined and placed in an electric furnace for high-temperature sintering. The sintering process includes sequential heating and cooling treatments, specifically: heating from room temperature to 250℃ at a heating rate of 4℃ / min and holding for 3h; heating to 500℃ at a heating rate of 4℃ / min and holding for 1h; heating to 900℃ at a heating rate of 3℃ / min and holding for 1h; heating to 1350℃ at a heating rate of 3℃ / min and holding for 1h; heating to 1620℃ at a heating rate of 1℃ / min and holding for 6h; cooling to 800℃ at a heating rate of 8℃ / min and cooling to room temperature in the furnace; finally, after fine processing and polishing, ceramic material is obtained.
[0073] Example 3
[0074] This embodiment provides a method for preparing alumina ceramic materials, including the following steps:
[0075] (1) Weigh aluminum oxide, chromium oxide, magnesium oxide, silicon dioxide, strontium oxide and manganese carbonate in a mass ratio of 92:2:1:3:0.5:1.5, with a total mass of 75g, and mix them to obtain a solid mixture;
[0076] (2) The solid mixture was calcined at 800℃ for 3h, and 120mL of deionized water, 0.04g of polydimethylsiloxane with a mass concentration of 30% and polymethyl methacrylate (CE-64) with a mass concentration of 30% were added. When adding CE-64, the viscosity was measured dropwise by a rotational viscometer until the viscosity decreased to 3826mPa·s. The mixture was ball-milled for 30h using a planetary ball mill. The slurry was taken out, and 3.5g of polyvinyl alcohol was added. The mixture was then granulated using a spray granulator to obtain powder with a particle size of 50μm-120μm.
[0077] (3) The above powder is loaded into a dry-pressed cylindrical mold, placed on a vibration platform and vibrated at a frequency of 15Hz, and then transferred to a dry-pressing equipment for dry-pressing. The pressure of the dry press is 90MPa and the holding time is 5min. The dry-pressed round block is then removed.
[0078] (4) After forming, the green body is machined into a green body with a round hole and placed in an electric furnace for high-temperature sintering. The sintering process includes sequential heating and cooling treatments, specifically: heating from room temperature to 260℃ at a heating rate of 1℃ / min and holding for 2h; heating to 600℃ at a heating rate of 1℃ / min and holding for 2h; heating to 900℃ at a heating rate of 1℃ / min and holding for 0.75h; heating to 1300℃ at a heating rate of 1℃ / min and holding for 1h; heating to 1450℃ at a heating rate of 5℃ / min and holding for 2h; cooling to 800℃ at a heating rate of 3℃ / min and cooling to room temperature in the furnace; finally, after fine processing and polishing, the ceramic material is obtained.
[0079] Example 4
[0080] This embodiment provides a method for preparing alumina ceramic materials, including the following steps:
[0081] (1) Weigh aluminum oxide, chromium oxide, calcium oxide, silicon dioxide, titanium oxide, barium oxide, strontium oxide and manganese carbonate in a mass ratio of 90:4:1.5:2:0.5:0.5:0.5:1, with a total mass of 75g, and mix them to obtain a solid mixture;
[0082] (2) The solid mixture was calcined at 600℃ for 6 hours, and 150 mL of deionized water, 0.04 g of polyoxypropylene with a mass concentration of 30% and sodium polyacrylate with a mass concentration of 35% were added. When adding sodium polyacrylate, the viscosity was measured dropwise by a rotational viscometer until the viscosity decreased to 3566 mPa·s. The mixture was then ball-milled for 34 hours using a planetary ball mill. The slurry was then removed, and 3.5 g of sodium carboxymethyl cellulose was added. The mixture was then granulated using a spray granulator to obtain powder with a particle size of 40 μm-110 μm.
[0083] (3) The above powder is loaded into an isostatic square silicone mold, placed on a vibration platform and vibrated at a frequency of 25Hz, and then transferred to an isostatic pressing equipment for isostatic pressing molding; wherein, the isostatic pressing pressure is 150MPa and the holding time is 10min.
[0084] (4) After forming, the green body is machined into a green body with a round hole and placed in an electric furnace for high-temperature sintering. The sintering process includes sequential heating and cooling treatments, specifically: heating from room temperature to 250℃ at a heating rate of 3℃ / min and holding for 6 hours; heating to 550℃ at a heating rate of 2℃ / min and holding for 3 hours; heating to 950℃ at a heating rate of 2.5℃ / min and holding for 1 hour; heating to 1350℃ at a heating rate of 5℃ / min and holding for 0.75 hours; heating to 1550℃ at a heating rate of 3℃ / min and holding for 3 hours; then cooling to 1000℃ at a heating rate of 1℃ / min and cooling to room temperature in the furnace; finally, after fine processing and polishing, the ceramic material is obtained.
[0085] Example 5
[0086] This embodiment provides a method for preparing alumina ceramic material, which is basically the same as the steps in Embodiment 2, except that the mass ratio of titanium oxide to strontium oxide is 0.05:1.45.
[0087] Example 6
[0088] This embodiment provides a method for preparing alumina ceramic material, which is basically the same as the steps in Embodiment 1, except that the temperature is increased to 1580℃ at a heating rate of 4℃ / min.
[0089] Comparative Example 1
[0090] This comparative example provides a method for preparing alumina ceramic material, which is basically the same as the steps in Example 1, except that titanium oxide is replaced with alumina.
[0091] Comparative Example 2
[0092] This comparative example provides a method for preparing alumina ceramic material, which is basically the same as the steps in Example 1, except that chromium oxide is replaced with alumina.
[0093] Comparative Example 3
[0094] This comparative example provides a method for preparing alumina ceramic material, which is basically the same as the steps in Example 1, except that manganese carbonate is replaced with alumina.
[0095] Experimental Example 1
[0096] The ceramic materials prepared in Examples 1-6 and Comparative Examples 1-3 were tested for density using Archimedes' drainage method, for air leakage rate using SJ / T 11583-2016, for Rockwell hardness using GB / T230-91, for wear resistance using ASTM G105-2016, and for grain size using the area method. The results are shown in the table below.
[0097] Corrosion resistance test: The samples of ceramic materials prepared in Example 1 were subjected to acid and alkali resistance tests. First, 62.3422g of ceramic sample material was weighed and the surface morphology after polishing was observed. Then, the ceramic material was placed in 1mol / L sulfuric acid solution and 1mol / L sodium hydroxide solution, respectively, and kept at a constant temperature of 50℃ for 24h, 48h, and 72h. The surface morphology was observed. The ceramic material remained dense. The mass change was measured and found to be 0.0021g, 0.0014g, and 0.0018g, respectively. The loss was ≤0.01g, indicating that the ceramic material prepared by this invention has good corrosion resistance.
[0098] Table 1. Performance test results of ceramic materials prepared in each embodiment and comparative example.
[0099]
[0100]
[0101] As can be seen from the table above, the ceramic materials prepared in Examples 1-6 have high density and small average grain size, and all other properties meet the national standards. However, in Example 5, the strontium oxide content was too high, and some strontium oxide accumulated in the interstitial spaces, affecting the main crystalline phase and producing a second strontium oxide phase, which led to a decrease in density. In Example 6, the temperature was continuously increased without a heat preservation section, and the pores could not be completely discharged, resulting in a ceramic material with more pores, which led to a decrease in density. In Comparative Example 1, titanium oxide was replaced with alumina, and chromium oxide (Cr2O3) was oxidized to form volatile CrO3. Chromium oxide could not be completely dissolved with alumina, resulting in lower density and compactness of the ceramic material. In Comparative Example 2, chromium oxide was replaced with alumina, similar to a common 95% alumina system. No chromium oxide formed a substitutional solid solution with alumina, and the main crystalline phase was alumina, resulting in decreased strength, decreased hardness, and poor wear resistance.
[0102] Experimental Example 2
[0103] The ceramic materials prepared in Examples 1-6 and Comparative Examples 1-3 were metallized. The specific steps were as follows: First, the ceramic substrate was processed into a tensile standard part, the surface of the ceramic substrate was polished, and a metallizing paste was applied to the surface by screen printing. The metallizing paste was a commonly used paste in the active molybdenum-manganese method. After drying, it was sintered at 1400°C in a wet hydrogen atmosphere. The sample was taken out, nickel was deposited by electrochemical method, and finally Kovar alloy was brazed to the obtained sample at 1000°C.
[0104] The tensile strength of the metallized ceramic material was tested according to SJ / T 3326-2016, the glass phase content was tested by XRD, and the withstand voltage test was performed in a vacuum withstand voltage test device. The voltage values of the first surface flashover phenomenon were compared. The results are shown in the table below.
[0105] Table 2. Performance test results of the ceramic materials prepared in each embodiment and comparative example after metallization.
[0106]
[0107]
[0108] As can be seen from the table above, the metallized ceramic materials prepared in Examples 1-6 have high tensile strength, all meeting the national standard ≥90MPa; Comparative Examples 1 and 2 have lower tensile strength due to the influence of grain size; Comparative Example 3 replaces manganese carbonate with alumina, resulting in higher resistivity of the ceramic material, lower flashover voltage, and poor breakdown performance.
[0109] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. An alumina ceramic material, characterized in that, The raw materials of the alumina ceramic material, by weight percentage, are: alumina 90wt%-92wt%, chromium oxide 2wt%-4wt%, dopant 0.4wt%-2wt%, sintering aid 1wt%-4wt%, silicon dioxide 1wt%-4wt%, and manganese carbonate 1wt%-2wt%. The dopant includes at least one of strontium oxide and titanium oxide; The dopant is strontium oxide, and the content of strontium oxide is 0.4wt%-1wt%; or, The dopant is titanium oxide, and the content of titanium oxide is 0.4wt%-1wt%; or, The dopants are strontium oxide and titanium oxide, wherein the content of strontium oxide is 0.4wt%-1wt%; and the content of titanium oxide is 0.4wt%-1wt%. The sintering aid includes at least one of calcium carbonate, calcium oxide, and magnesium oxide.
2. A method for preparing the alumina ceramic material according to claim 1, characterized in that, Includes the following steps: (1) Weigh the raw materials of the alumina ceramic material, mix them, and obtain a solid mixture; (2) The solid mixture is calcined, ball-milled, and granulated to obtain powder; (3) The powder is pressed and sintered to obtain the alumina ceramic material.
3. The method for preparing alumina ceramic material according to claim 2, characterized in that, The sintering process includes heating and cooling.
4. The method for preparing alumina ceramic material according to claim 3, characterized in that, The heating process includes raising the temperature to the first temperature zone of 200℃-260℃, the second temperature zone of 500℃-600℃, the third temperature zone of 800℃-1000℃, the fourth temperature zone of 1200℃-1400℃, and the fifth temperature zone of 1450℃-1650℃. The cooling process includes: cooling the temperature to 700℃-1000℃ and then cooling it to room temperature along with the furnace.
5. The method for preparing alumina ceramic material according to claim 4, characterized in that, The heating rates of the first temperature zone, the second temperature zone, the third temperature zone, the fourth temperature zone, and the fifth temperature zone are 1℃ / min-5℃ / min; And / or, the cooling rate is 1℃ / min-8℃ / min; And / or, the heat preservation time of the first temperature zone is 2h-6h; And / or, the heat preservation time in the second temperature zone is 1h-3h; And / or, the heat preservation time of the third temperature zone and the fourth temperature zone is 0.5h-1h; And / or, the heat preservation time of the fifth temperature zone is 2h-6h.
6. The method for preparing alumina ceramic material according to claim 2, characterized in that, In step (2), after the solid mixture is calcined, defoamer, dispersant and deionized water are added and mixed, then ball milled, and then binder is added for granulation to obtain powder.
7. The method for preparing alumina ceramic material according to claim 6, characterized in that, The defoamer includes at least one of tributyl ester solution, polydimethylsiloxane solution, and polyoxypropylene solution; And / or, the dispersant comprises at least one of polyammonium methacrylate solution, polyacrylic acid solution, and sodium polyacrylate solution; And / or, the adhesive includes at least one of polyvinyl alcohol, polyethylene glycol, and sodium carboxymethyl cellulose; And / or, the mass ratio of the solid mixture, the defoamer, the deionized water, and the binder is 100:0.05-0.1:150-200:3-5; And / or, add the dispersant until the viscosity drops below 4000 mPa·s, then stop adding the dispersant; And / or, the mass concentration of the defoamer is 30%-40%; And / or, the mass concentration of the dispersant is 30%-35%; And / or, the calcination temperature is 600℃-800℃, and the calcination time is 3h-6h; And / or, the ball milling time is 30h-36h; And / or, the particle size of the powder is 40μm-130μm.
8. The method for preparing alumina ceramic material according to claim 3, characterized in that, The pressing and molding step is at least one of isostatic pressing and dry pressing. And / or, prior to the molding process, a compaction step is further included, wherein the compaction frequency is 15Hz-30Hz; And / or, after the cooling process, the process may further include finishing and polishing steps.
9. The method for preparing alumina ceramic material according to claim 8, characterized in that, The isostatic pressing pressure is 150MPa-300MPa, and the holding time is 3min-10min; And / or, the pressure of the dry pressing is 50MPa-90MPa, and the holding time is 3min-5min.
10. A ceramic material for a relay housing, characterized in that, The alumina ceramic material includes the alumina ceramic material according to claim 1, or the alumina ceramic material prepared by the preparation method according to any one of claims 2-9.
11. A relay, characterized in that, Includes the ceramic material for the relay housing as described in claim 10.
Citation Information
Patent Citations
Preparation process of alumina ceramic material
CN121063925A